A Study to Assess the Risk of Cariovascualar Disease among Post- Menopausal Apartment Dwelling Women (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Background: The permanent cessation of ovarian function and the transition of a woman from a reproductivetoa nonreproductive life is defined as Menopause. This period is characterized by remarkable changes inmenstruationand hormonal patterns as well as psychological and physiological symptoms.Objectives: The objectives of this study was to assess the Body-Mass Index, Waist-Hip Ratio, Submaximal AerobicCapacity, Ankle-Brachial Index and Quality of Life using the SF-12 questionnaire among post-menopausalapartment dwelling women.Design: Descriptive StudyMethods: 110 subjects meeting the inclusion and exclusion criteria were included in the study. The subjects wereassessed based on the screening tools Body-Mass Index (BMI) and Waist- Hip Ratio. The outcome tools usedto assess the risk of cardiovascular disease among post-menopausal apartment dwelling women were Ankle-Brachial Index (ABI), Six-Minute Walk Test (6MWT) and health related quality of life SF-12 Questionnaire.Results: Out of 110 subjects, 59 subjects had a BMI of 25-29.9 kg/m2 and 36 subjects had a BMI of ≥30 kg/m2.56 (51%)subjects had substantially higher waist- hip ratio (≥0.85 cm). 61(55.5%) subjects had mild to moderate peripheralarterial disease on left side and 67 (60.9%) subjects had mild-moderate peripheral arterial disease on right side.The range of 6MWD is between 490-900 m. The correlation between MCS 12 and PCS 12 has an intermediate poorcorrelation.Conclusion: The study shows that Post- Menopausal Apartment Dwelling Women are at risk of CardiovascularDisease.
Keywords: Menopause, Cardiovascular Diseases, Body-Mass Index,Waist- Hip Ratio, Six- Minute Walk Test, Health Related Quality of Life, SF-12 Questionnaire